Handbook of Rheological Additives - Wypych, George (ChemTec Publishing, 2022)
Handbook of Rheological Additives covers how these additives are commonly applied in a wide range of industries, providing readers with information on over 300 organic and inorganic additives.This information is presented in individual tables for each product, whether commercial or generic.